Kedudukan Hukum Alat Bukti Petunjuk Rekaman Cctv Oleh Hakim Dalam Menjatuhi Hukuman Pidana (Studi Kasus Putusan NO.141/PID.B/2018/PN SLW/Pengadilan Negri Slawi) - Ika Yanuarita; Wenny Megawati (UNES Law Review, 2023)
This research discusses the legal position of CCTV footage evidence by judges in sentencing criminal law (Case Study of Decision No.141/PID.B/2018/PN SLW/Slawi District Court). The type used in this research is normative juridical. Normative juridical where law is conceptualized as what is written in statutory regulations (law in books) or law is conceptualized as rules or norms which are benchmarks for human behavior that are considered appropriate. In this case study, the authors examine decisions related to the research topic, namely Decision No.141/PID.B/2018/PN SLW/Slawi District Court. The decision is a decision in a criminal case of theft using Close Circuite Television (CCTV) evidence. The data analysis method used in this study is a qualitative analysis method. Data obtained from the results of the literature, juridically, will be presented and analyzed based on the theory of criminal law and applicable legal regulations, so that from here correct and objective conclusions will be obtained about the legal position of evidence of CCTV recording instructions by judges in sentencing criminal sentences. The results of this study are: 1) The position of CCTV footage as evidence in the criminal justice process in the Slawi District Court case study does not include evidence. However, the CCTV along the toll road up to Tegal was used as evidence by the Slawi District Court and the public prosecutor because there was information from experts; and 2) The judge's consideration of the CCTV footage as valid evidence in a crime in the decision of the Panel of Judges makes the CCTV footage a reinforcement of the statements of witnesses presented in the investigation and supported by expert testimony.